Analysis of the implementation effect of the operating room nursing safety management model based on Heinrich’s law - Yanru Wu; Mengmin Jing; Haiqin Yang; Juan Liu; Tiantian Zhang; Hui Zhu; Yajuan Yang; Chunyan Gao (BMC Surgery)
Abstract Objective The study evaluates the clinical value of the operating room nursing safety management model based on Heinrich’s law. Methods A quasi-experimental design with a historical control group was conducted at Changzheng Hospital. A total of 240 surgical patients (pre-intervention: n = 120, December 2021–2022; post-intervention: n = 120, January–December 2023) were recruited via convenience sampling. The intervention included standardized protocols, mobile nursing systems, electronic specimen labeling, and equipment management. Quantitative outcomes were analyzed using χ² tests (adverse events), independent t-tests (nursing competency scores), and logistic regression (risk factors). Patient satisfaction was assessed via a validated self-report questionnaire. Results The results showed a significant reduction in the incidence of operating room nursing safety accidents and a significant improvement in the specific nursing, identification, management of specimens, health education, safety awareness and operational skills of the nursing staff after the implementation of the operating room nursing safety management model based on Heinrich’s law (P < 0.05).The management model implemented in the operating room had a positive impact on nursing safety, as evidenced by the significant improvement in patient satisfaction (P < 0.05). Logistic multifactorial regression analysis identified several key factors that affect nursing care safety in the operating room, including the nursing staff’s business ability, legal awareness, the operating room environment, and the management system. Conclusion The Heinrich’s law-based model effectively enhances perioperative safety by reducing errors, improving nursing competency, and increasing patient satisfaction. Clinically, we recommend integrating standardized protocols with mobile alert systems, prioritizing staff training on legal and technical skills, and optimizing equipment workflows. Future studies should validate these findings in multicenter trials and assess long-term cost-effectiveness.